How do we solve this one ? Solve for x : - (a+b)x + 2b =0

Follow Math Help Forum on Facebook and Google+

Originally Posted by sabyasachi How do we solve this one ? Solve for x : - (a+b)x + 2b =0 Use the quadatic formula: a = a - b, b = -(a + b), c = 2b. Ohhhhh ....... that doesn't make sense does it? Why is that I wonder ......? Let me start again: Use the quadatic formula: A = a - b, B = -(a + b), C = 2b. Get it?

Originally Posted by sabyasachi How do we solve this one ? Solve for x : If use the quadratic formula, if , then the solution is . RonL

Thank you.

View Tag Cloud